The impact of hepatitis C on labor force participation, absenteeism, presenteeism and non-work activities - Marco DiBonaventura; Jan-Samuel Wagner; Yong Yuan; Gilbert L’Italien; Paul C. Langley; W. Ray Kim (2011)
Between 2.7 and 3.9 million people are currently infected with the hepatitis C virus (HCV) in the United States. Although many studies have investigated the impact of HCV on direct healthcare costs, few studies have estimated the indirect costs associated with the virus using a nationally-representative dataset.Using data from the 2009 United States (US) National Health and Wellness Survey, patients who reported a hepatitis C diagnosis (n = 695) were compared to controls on labor force participation, productivity loss, and activity impairment after adjusting for demographics, health risk behaviors, and comorbidities. All analyses applied sampling weights to project to the population.Patients with HCV were significantly less likely to be in the labor force than controls and reported significantly higher levels of absenteeism (4.88 vs. 3.03%), presenteeism (16.69 vs. 13.50%), overall work impairment (19.40 vs.15.35%), and activity impairment (25.01 vs. 21.78%). A propensity score matching methodology replicated many of these findings.While much of the work on HCV has focused on direct costs, our results suggest indirect costs should not be ignored when quantifying the societal burden of HCV. To our knowledge, this is the first study which has utilized a large, nationally-representative data source for identifying the impact of HCV on labor force participation and work and activity impairment using both a propensity-score matching and a regression modeling framework.All data were patient-reported (including HCV diagnosis and work productivity), which could have introduced some subjective biases.